Comparative Evaluation of Tissue Damage in the Maxillofacial Region When Using Oral-Facial Piercing - Savelieva Н. М.; Shatov П. О. (Actual Dentistry, 2025)
Summary. Piercing of the orofacial region is widespread among young people as a form of self-expression and aesthetic modification. Most often, piercings are performed on the tongue, lips, and frenulum, which is associated with the risk of dental complications such as inflammatory changes, gum recession, damage to teeth and soft tissues, as well as systemic infections, including endocarditis and viral diseases. The study aimed to conduct a comparative assessment of periodontal and soft-tissue damage in the oral cavity resulting from orofacial piercings at various locations and made from different dental alloys. Results. The most common locations of piercings were tongue—42.7%, lower lip—23.5%, upper lip—16.2%, and upper lip frenulum—17.6%. The frequency of complications depended on the jewelry material: medical steel—76.2%; titanium—22.2%; silver—23.0%; gold—31.3%; and allergies were observed only with steel (4.8%). Perifocal inflammatory changes most often occurred with steel jewelry (22.7%) and least often with titanium (5.9%) and gold (4.6%). The location of the piercing did not significantly affect complications, but the tongue was associated with more inflammatory reactions. Hygiene (OHI-S) and gum inflammation (PMA) were worse with steel (OHI-S 1.87±0.16; PMA 10.81±0.42) compared to gold, silver, and titanium (p < 0.05). Inflammatory changes in the gums were observed in 72% and recession in 96%, with an average depth of 1.47 mm. With tongue piercing, recession formed mainly on the lingual surface; with lip piercing, on the side of contact with the gums. Conclusion. Piercing of the orofacial region increases the risk of local complications, including inflammatory changes, gum recession, and soft-tissue damage. The highest complication rate was observed with medical steel (76.2%), while titanium and gold showed the best biocompatibility.